Working through conflict : strategies for relationships, groups, and organizations - Folger, Joseph P., 1951-; Poole, Marshall Scott, 1951-; Stutman, Randall K., 1957- (New York : Longman, 1997)
Focusing on the whole range of conflict settings - interpersonal, group, and organizational - Working Through Conflict, Third Edition, provides an introduction to conflict management that is firmly grounded in current theory and research. The text encompasses a wide range of theoretical perspectives and includes timely, up-to-date coverage of the role of third parties in conflict resolution. Numerous, highly practical case studies clarify theoretical content and make it accessible to a broad audience. Updated to reflect the latest research and theory, the third edition of Working Through Conflict includes new information on culture and conflict and the impact of cultural differences. Prefaced by new "Imagine Yourself..." questions that encourage the reader to assume the role of one of the disputants, each case study also ends with questions that highlight the theory behind the case and encourage classroom discussion.
Introduction: Conflict and Interaction -- Ch. 1. Traditional Perspectives on Conflict -- Ch. 2. Explaining Conflict Processes -- Ch. 3. The Role of Communication in Conflict -- Ch. 4. Power: The Architecture of Conflict -- Ch. 5. Face-Saving -- Ch. 6. Climate and Conflict Interaction -- Ch. 7. Doing Conflict: Styles, Strategies, and Tactics -- Ch. 8. Changing Conflict Dynamics -- Ch. 9. Third Party Intervention.
Includes bibliographical references (p. 292-311) and index.
Keywords: Social conflict; Conflict (Psychology); Conflict management; Social interaction; Interpersonal conflict